Diaspora, authenticity and the imagined past. (September 2017) - Bryce, Derek; Murdy, Samantha; Alexander, Matthew
Highlights: Explores authentication through the phenomenon of ancestral tourism in Scotland. Reveals authenticity as a process of co-creation driven by tourists and heritage professionals. Proposes that 'authentically imagined pasts' in the diaspora are part of this process. Understands authentication as a historically contingent process. Explores professional heritage practice responds to the ancestral market. Abstract: Ancestral tourism in Scotland, a sector of the heritage tourism market sensitive to consumer personalisation, has particular propensities towards process-driven co-created experiences. These experiences occur within existing categories of object-based and existential notions of authenticity alongside an emergent category of the 'authentically imagined past'. The latter of these modes reveals a complex interplay between professionally endorsed validation of the empirical veracity of objects, documents and places and deeply held, authentically imagined, narratives of 'home'. These narratives, built up in the Diaspora over centuries, drive new processes towards authenticity in tourism. We conducted 31 interviews across 27 sites throughout Scotland with curators, archivists, and volunteers to explore these notions of authenticity within the ancestral tourism context.